2022
DOI: 10.3389/fonc.2022.857968
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion-Localized SND1 Promotes Mitophagy and Liver Cancer Progression Through PGAM5

Abstract: Staphylococcal nuclease domain-containing protein 1 (SND1) is an evolutionarily conserved multifunctional protein that functions mainly in the nucleus and cytoplasm. However, whether SND1 regulates cellular activity through mitochondrial-related functions remains unclear. Herein, we demonstrate that SND1 is localized to mitochondria to promote phosphoglycerate mutase 5 (PGAM5)-mediated mitophagy. We find that SND1 is present in mitochondria based on mass spectrometry data and verified this phenomenon in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…This indicates that our results are reproducible and reliable to some extent. A recent study validated PGAM5 function, thereby providing sufficient evidence to support the reliability and reproducibility of our results [ 68 ]. In summary, our study not only has a novelty but also provides further support for previous research.…”
Section: Discussionsupporting
confidence: 73%
“…This indicates that our results are reproducible and reliable to some extent. A recent study validated PGAM5 function, thereby providing sufficient evidence to support the reliability and reproducibility of our results [ 68 ]. In summary, our study not only has a novelty but also provides further support for previous research.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, the above data suggest that mitophagy, mediated by PINK1 and NIPSNAP1, plays a crutial role in liver fibrosis. However, the mitophagy has a context‐dependent impact in different liver diseases (Li et al, 2020; Liang et al, 2022). On one hand, mitophagy supports hepatic fibrogenesis (Dou et al, 2021; Kang et al, 2016), while mitophagy limits liver fibrosis (Qiu et al, 2019; Wu et al, 2020) on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in response to combined treatments of the mitochondrial uncoupler of oxidative phosphorylation and glucose deprivation, SND1 was imported into mitochondria and activated dynamin-related protein 1 (DRP1)-mediated mitophagy to promote HCC cell proliferation and tumor growth both in vitro and in vivo. 10 SND1 was also reported to enhance cholesterol synthesis and deregulate cholesterol homeostasis in hepatoma cells. 14 In current study, we reported a novel role of SND1 in regulating aerobic glycolysis in liver cancer cells, which contributes to liver cancer cell malignancies and sorafenib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies indicated SND1 had effects on material and energy metabolism of HCC cells. For example, in response to combined treatments of the mitochondrial uncoupler of oxidative phosphorylation and glucose deprivation, SND1 was imported into mitochondria and activated dynamin‐related protein 1 (DRP1)‐mediated mitophagy to promote HCC cell proliferation and tumor growth both in vitro and in vivo 10 . SND1 was also reported to enhance cholesterol synthesis and deregulate cholesterol homeostasis in hepatoma cells 14 .…”
Section: Discussionmentioning
confidence: 99%